Finance and Development, September 1986. (Finance and Development; Finance and Development, 1986)
This paper examines the trade and pricing policies in world agriculture. In the United States, the government pays farmers not to grow cereals and in the European Community, farmers are paid to grow more. Many have raised nominal producer prices but followed macroeconomic and exchange rate policies that left real producer prices unchanged or lower than before. Many have set up complex systems of producer taxation, and then established equally complex and frequently ineffectual systems of subsidies for inputs to offset that taxation.